Correlation between the number of setted up hypertenses in hiperdia program and the enlargement of family's health strategy: descriptive study - Ellen Tamira Alves de Lima; Isabelle Gouveia Muniz; Rafaela Ferreira Santos; Simone Maria Muniz da Silva Bezerra; Carla Campos Muniz Medeiros; Inácia Sátiro Xavier de França (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2009)
To correlate the number of setted up hypertenses in Hiperdia Program and the enlargement of Family's Health Strategy from 2000 to 2008. Ecological study of the type time series, of quantitative approach. There were used data of the number of set up hypertenses in the Hiperdia Program and the number of family health teams from 2000 to 2008, available by the Health Ministry by Internet (www.datasus.gov.br). There were built two linear printers of variables evolution along the years selected and when the averages of growth of the parameters chosen for comparison and discussion were calculated. The correlation was calculated by the coefficient of Spearman. The evolution number of setted up hypertenses in Hiperdia Program presented standard of linear growth with exception in 2007 who presented decrease. The number of family health teams already presented linear growth during the whole period. The coefficient of Spearman demonstrated strong correlation between the enlargement of the Family's Health Strategy and the increase of the number of setted up hypertenses in Hiperdia Program. The incentive to the enlargement of Family's Health Strategy covering seems provide a bigger attention to health for hypertense population.